Search engines: a first step to finding information: preliminary findings from a study of observed searches - A.D. Madden; B. Eaglestone; N.J. Ford; M. Whittle (Information Research: An International Electronic Journal)
Introduction. This is a working paper which aims to present the preliminary results of a study into the search behaviour of the general public. The paper reports on the findings of the first six months of an eighteen-month data collection excercise. Method. . Detailed observations were made of nine volunteers, engaged on a variety of search tasks. Some of the tasks were self-selected, others were set by the researchers. Most tasks however, were designed to enable the volunteers to search within their own areas of interest and expertise. Analyses. A set of 'search dimensions' is proposed and qualitative findings based on these are presented. In addition, some initial quantitative findings are discussed. Result. Findings to date suggest that the best search strategy is a combination of simplicity and scrutiny. Volunteers who entered a few search terms but then carefully studied the results, appeared to be more successful than those who attempted to be prescriptive and entered a long series of terms.